Energy compensation in the real world: Good compensation for small portions of chocolate and biscuits over short time periods in complicit consumers using commercially available foods. (1st February 2015) - Appleton, Katherine M.; McKeown, Pascal P.; Woodside, Jayne V.
Highlights: Studies using covert food manipulations tend to demonstrate poor energy compensation. We studied responses to chocolate, biscuits and fruit bars using overt manipulations. We demonstrate good compensation for familiar food portions over short time periods. Studies using covert manipulations may have limited transfer to real world scenarios. Abstract: While investigations using covert food manipulations tend to suggest that individuals are poor at adjusting for previous energy intake, in the real world adults rarely consume foods of which they are ill-informed. This study investigated the impact in fully complicit consumers of consuming commercially available dark chocolate, milk chocolate, sweet biscuits and fruit bars on subsequent appetite. Using a repeated measures design, participants received four small portions (4 × 10–11 g) of either dark chocolate, milk chocolate, sweet biscuits, fruit bars or no food throughout five separate study days (counterbalanced in order), and test meal intake, hunger, liking and acceptability were measured. Participants consumed significantly less at lunch following dark chocolate, milk chocolate and sweet biscuits compared to no food (smallest t(19) = 2.47, p = 0.02), demonstrating very good energy compensation (269–334%). No effects were found for fruit bars (t(19) = 1.76, p = 0.09), in evening meal intakes (F(4, 72) = 0.62, p = 0.65) or in total intake (lunch + evening meal + food portions) (F(4, 72) = 0.40, p = 0.69). No differences between conditions were found in measures of hunger (largest F(4, 76) = 1.26, p = 0.29), but fruit bars were significantly less familiar than all other foods (smallest t(19) = 3.14, p = 0.01). These findings demonstrate good compensation over the short term for small portions of familiar foods in complicit consumers. Findings are most plausibly explained as a result of participant awareness and cognitions, although the nature of these cognitions cannot be discerned from this study. These findings however, also suggest that covert manipulations may have limited transfer to real world scenarios.